Quantification of carbonic anhydrase gene expression in ventricle of hypertrophic and failing human heart - Álvarez, Bernardo Víctor (2013)
Background: Carbonic anhydrase enzymes (CA) catalyze the reversible hydration of carbon dioxide to bicarbonate in mammalian cells. Trans-membrane transport of CA-produced bicarbonate contributes significantly to cellular pH regulation. A body of evidence implicates pH-regulatory processes in the hypertrophic growth pathway characteristic of hearts as they fail. In particular, Na+/H+ exchange (NHE) activation is pro-hypertrophic and CA activity activates NHE. Recently Cardrase (6-ethoxyzolamide), a CA inhibitor, was found to prevent and revert agonist-stimulated cardiac hypertrophy (CH) in cultured cardiomyocytes. Our goal thus was to determine whether hypertrophied human hearts have altered expression of CA isoforms.Methods: We measured CA expression in hypertrophied human hearts to begin to examine the role of carbonic anhydrase in progression of human heart failure. Ventricular biopsies were obtained from patients undergoing cardiac surgery (CS, n = 14), or heart transplantation (HT, n = 13). CS patients presented mild/moderate concentric left ventricular hypertrophy and normal right ventricles, with preserved ventricular function; ejection fractions were ~60%. Conversely, HT patients with failing hearts presented CH or ventricular dilation accompanied by ventricular dysfunction and EF values of 20%. Non-hypertrophic, non-dilated ventricular samples served as controls.Results: Expression of atrial and brain natriuretic peptide (ANP and BNP) were markers of CH. Hypertrophic ventricles presented increased expression of CAII, CAIV, ANP, and BNP, mRNA levels, which increased in failing hearts, measured by quantitative real-time PCR. CAII, CAIV, and ANP protein expression also increased approximately two-fold in hypertrophic/dilated ventricles.Conclusions: These results, combined with in vitro data that CA inhibition prevents and reverts CH, suggest that increased carbonic anhydrase expression is a prognostic molecular marker of cardiac hypertrophy.